(untitled) (Materiali di Estetica. Terza serie, 2023)
The Greeks represent themselves and the κóσμος according to chromatic categories linked to luministic variations and to the qualities of the object of which colour is a property. While placing chromatic perception within the synesthetic experience, the Greeks do not make colour a mere sensory vehicle but a form of θεωρεῖν. Particularly in the poetic text, the chromatic signifier expresses multiple, often contrasting symbolic and psycho-affective nuances, which allow us to identify the profound isotopies concealed within it. In the present essay we discuss the colours of the Trachiniae, whose brilliant or dull hues range between green and red, green and mottled, white and black. By intersecting several semantic values, they do not only convey an overall vision of the text and of the scenic apparatus but also amplify the degree of subjectivity of the protagonists with their irrepressible and devastating passions.